Mesoporous cerium oxide-coated upconversion nanoparticles for tumor-responsive chemo-photodynamic therapy and bioimaging. Issue 37 (8th August 2019) - Jia, Tao; Xu, Jiating; Dong, Shuming; He, Fei; Zhong, Chongna; Yang, Guixin; Bi, Huiting; Xu, Mengshu; Hu, Yingkui; Yang, Dan; Yang, Piaoping; Lin, Jun
Abstract : A hollow structured biophotocatalyst comprising an UCNP core and mesoporous cerium oxide shell was constructed to realize oxygen self-efficient photodynamic therapy upon 980 nm laser irradiation under multiple imaging guidance. Abstract : Long-term tumor hypoxia has always been a huge obstacle for oxygen dependent photodynamic therapy (PDT) and anticancer drug chemotherapy. Herein, a hollow-structured biophotocatalyst was developed by coating mesoporous cerium oxide (mCeO x ) on upconversion nanoparticles (UCNPs, NaGdF4 :Yb, Tm@NaGdF4 ), and it can be initialized with a near-infrared (NIR) laser to achieve PDT with O2 compensation by decomposing the endogenous H2 O2 in the tumor microenvironment. A NIR laser with a long wavelength has low phototoxicity to biotissue, and the core–inert shell structured UCNPs can efficiently convert the NIR photons into ultraviolet (UV) light, which can further trigger CeO x to produce reactive oxygen species (ROS). Moreover, the internal space of UCNPs@mCeO x is ideal for storing chemotherapeutic doxorubicin (DOX), and adequate O2 plays a key role in alleviating drug fastness via chemotherapy in hypoxic tumors, thereby strengthening the synergy between PDT and chemotherapy. After being injected into tumor-bearing mice intravenously, the nanomedicine was able to reach the tumor via an enhanced permeability and retention (EPR) effect. In addition, the capability to use the developed nanosystem in computed tomography (CT), magnetic resonance (MR) and upconversion luminescence (UCL) imaging was validated. Significantly, the NIR laser irradiated nanomedicine exhibits an excellent anticancer effect, implying promising theranostic applications.